The Participation of Austria and Hungary in the Framework Programmes for Research and Technological Development of the European Union. A Comparative Analysis - Ágota Dávid (Romanian Journal of European Affairs)
The significance of the framework programmes for research and technological development of the European Union is constantly increasing. Horizon 2020, the Eighth Framework Programme with its 80 billion euro budget is a very important player in science funding. At the same time, due to the economic crisis and limited state budget for research and technology, national governments gladly encourage their scientists to apply for funds on the European level. Especially if they want to cooperate and carry out research internationally. So, as a surprising result, increasing amounts for funding result in more fierce competition. How do new and old Member States perform in this competition? The study will show this through the example of the performance of one old Member State – Austria – and one new Member State – Hungary. In the paper, first the history of framework programmes will be summarised, then the analysis of STI statistics about participation, success rates and financial contribution in retained proposals will follow. The difference in success rates might derive from various factors, including public and business expenditure on R&D, number of researchers, governmental support schemes or the more active involvement of innovative small and medium-sized enterprises.